INNOVATING BY INTEGRATING: POLICIES FOR RESILIENT AND ATTRACTIVE CITIES - Sepe, Marichela (BDC. Bollettino Del Centro Calza Bini, 2016)
In 2011, the European Commission publishes the “Cities of Tomorrow. Challenges, visions, ways forward” report, introducing the integrated approach to the urban policies, whose sectoriality has caused different problems further increased by the economic crisis. The threats identified within the report regard the demographic decline, the climate change, the social segregation, the difficult competitiveness caused by the economic decrease. The aim of this paper is illustrating the most significant parts of “Cities of Tomorrow” which remains one of the most futurist documents in that sense. In order to present a best practice, the description of both integrated urban strategies and design solutions which Rotterdam are currently carrying out, taking into account innovation and sustainability aspects, will complete the paper. Keywords: sustainability, integrated policies, innovation